DIGITAL MEDIA AS A MEANS OF PROMOTING AND STRENGT HENING SUSTAINABLE TOURISM IN BANJARBARU CITY, SOUTH KALIMANTAN - Mahmuda, Luqman Abdulloh; Kusuma, Andri Haryono Awalokta; Solikah, Umi Nur (Smart Education, 2025)
Abstract: This article analyzes the role of digital media as a means of promoting and strengthening sustainable tourism practices in Banjarbaru City, South Kalimantan. The research was conducted using a descriptive qualitative approach and digital content analysis, as well as case studies of three leading destinations: Lake Seran, Mentaos Pine Forest, and Banua Botanical Garden. Data collection included in-depth interviews (n=25), participant observation, and analysis of 450 destination-related social media posts on Instagram, TikTok, and YouTube. The results indicate that: (1) digital media is effective in increasing destination visibility and attracting visitors; (2) sustainability-themed content (eco-storytelling, conservation education) strengthens the destination's image as environmentally friendly; (3) collaboration between the government and the influencer community contributes significantly to the dissemination of sustainability messages; and (4) the main challenges are unequal digital literacy, limited promotional budgets, and fluctuating network infrastructure. The article concludes with practical policy recommendations for the Banjarbaru Tourism Office and local stakeholders to implement sustainable, data-driven digital promotion strategies.Keyword: creative economy;digital media;sustainable tourism.Abstrak: Artikel ini menganalisis peran media digital sebagai sarana promosi sekaligus penguatan praktik pariwisata berkelanjutan di Kota Banjarbaru, Kalimantan Selatan. Penelitian dilakukan dengan pendekatan kualitatif deskriptif dan analisis konten digital, serta studi kasus pada tiga destinasi unggulan: Danau Seran, Hutan Pinus Mentaos, dan Banua Botanical Garden. Pengumpulan data meliputi wawancara mendalam (n=25), observasi partisipatif, dan analisis 450 unggahan media sosial terkait destinasi pada platform Instagram, TikTok, dan YouTube. Hasil menunjukkan bahwa: (1) media digital efektif meningkatkan visibilitas destinasi dan mendatangkan kunjungan; (2) konten bertema keberlanjutan (eco storytelling, edukasi konservasi) memperkuat citra destinasi sebagai ramah lingkungan; (3) kolaborasi pemerintah komunitas influencer berkontribusi signifikan terhadap penyebaran pesan keberlanjutan; serta (4) tantangan utama adalah literasi digital yang belum merata, keterbatasan anggaran promosi, dan infrastruktur jaringan yang masih fluktuatif. Artikel menutup dengan rekomendasi kebijakan praktis bagi Dinas Pariwisata Banjarbaru dan pemangku kepentingan lokal untuk menerapkan strategi promosi digital yang berkelanjutan dan berbasis data.Kata kunci: ekonomi kreatif;media digital;pariwisata berkelanjutan.